Genomic Resources Notes accepted 1 June 2013–31 July 2013. (25th September 2013) - ,; Bensch, Staffan; Coltman, David W.; Davis, Corey S.; Hellgren, Olof; Johansson, Tomas; Malenfant, René M.; Moore, Stephen S.; Palinauskas, Vaidas; Valkiūnas, Gediminas
Abstract This article documents the public availability of (i) raw transcriptome sequence data, assembled contigs and UniProt BLAST hits from common crossbill (Loxia curvirostra) and Plasmodium relictum (lineage SGS1) obtained from a controlled infection experiment; and (ii) raw transcriptome sequence data and 66 596 SNPs for the white‐tailed deer (Odocoileus virginianus).